Web 2.0 Authoring Tools in Higher Education : New Directions for Assessment and Academic Integrity : Final Report. - Waycott, Jenny; Gray, Kathleen (Australian Learning and Teaching Council (ALTC), 2011)
Final report from a project that aimed to develop a set of guidelines formalising academic practices, standards and reporting relating to the use in higher education of Web 2.0 or social software for assessing student learning. Web 2.0 forms of authoring or content creation include blogging/microblogging, audio/video podcasting, social bookmarking, social networking, virtual worlds and wiki writing (eg WordPress, Twitter, Flickr, YouTube, Second Life, Delicious, Facebook, MediaWiki, etc). Increasingly these activities are being used to support students' learning in higher education. However, very little is known about appropriate academic practices for assessing students' work or authorship with Web 2.0 technologies. By identifying and addressing these issues, this project met a growing need in Australian institutional and disciplinary communities to establish and maintain good practice in the design and conduct of new forms of assessment. This project engaged a range of institutions, staff and students in collaborative activities to give shape and direction to improve teaching, tutoring and marking practices across institutions and disciplines, locally and nationally. It focused on the scope of assessment policy and procedures, the emphasis of library and learning skills support, the educational design of assessment activities, the management of student records, and the provision of educational technology services to support the Assessment of Student Web 2.0 Authoring. A website, a blog and a social bookmarking tool were developed to disseminate findings.